2012
DOI: 10.1007/s10646-012-0855-x
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved organic carbon reduces uranium toxicity to the unicellular eukaryote Euglena gracilis

Abstract: The influence of dissolved organic carbon (DOC), in the form of Suwannee River fulvic acid (SRFA), on uranium (U) toxicity to the unicellular eukaryote, Euglena gracilis (Z strain), was investigated at pH 6. In a background medium without SRFA, exposure of E. gracilis to 57 μg L(-1) U resulted in a 50% reduction in growth (IC(50)). The addition of 20 mg L(-1) DOC (as SRFA), reduced U toxicity 4 to 5-fold (IC(50) increased to 254 μg L(-1) U). This reduction in toxicity was also evident at more sensitive effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 40 publications
0
20
1
Order By: Relevance
“…Mechanisms Euglena uses to eliminate the toxic effects of cadmium, chromium mercury and zinc include increased synthesis of heavy metalchelating molecules with thiol groups and phytochelatins, together with metal sequestration into chloroplasts and mitochondria (Aviles et al, 2005;Garcia-Garcia et al, 2014;Lira-Silva et al, 2011;Mendoza-Cozatl et al, 2006). The effect of dissolved organic carbon on uranium toxicity in E. gracilis has also been investigated (Trenfield et al, 2012). Growth of Euglena in heavy metal containing acidic streams and polluted rivers of mining areas by sequestration of heavy metals suggests that these protists can be used as potent tools for bioremediation of heavy metal contaminated waters.…”
Section: Euglena Under Extreme Conditions and As An Organism For Biormentioning
confidence: 99%
“…Mechanisms Euglena uses to eliminate the toxic effects of cadmium, chromium mercury and zinc include increased synthesis of heavy metalchelating molecules with thiol groups and phytochelatins, together with metal sequestration into chloroplasts and mitochondria (Aviles et al, 2005;Garcia-Garcia et al, 2014;Lira-Silva et al, 2011;Mendoza-Cozatl et al, 2006). The effect of dissolved organic carbon on uranium toxicity in E. gracilis has also been investigated (Trenfield et al, 2012). Growth of Euglena in heavy metal containing acidic streams and polluted rivers of mining areas by sequestration of heavy metals suggests that these protists can be used as potent tools for bioremediation of heavy metal contaminated waters.…”
Section: Euglena Under Extreme Conditions and As An Organism For Biormentioning
confidence: 99%
“…The loss of motility and the rounding of the cells were described as a stress effect related to low pHvalues and/or metal toxicity [30], e.g. uranium [21]. At uranium concentrations > 300 g/L at pH 6 for Euglena gracilis it was observed that the cells changed shape from a healthy, long spindle form to a "tear-drop" or cyst-like Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 6/1/15 12:40 PM spherical shape [21].…”
Section: Bioaccumulation Of Uranium By Euglena Cellsmentioning
confidence: 99%
“…However, there was no information provided concerning the reaction mechanisms to immobilize uranium by the Euglena cells. Trenfield et al [21] studied the influence of dissolved organic carbon on uranium toxicity to Euglena gracilis at pH 6. Both groups [19,21], however, did not provide any information on the respective uranium speciation in the surrounding water and associated with Euglena cells.…”
Section: Introductionmentioning
confidence: 99%
“…Alteration of cell morphology of Euglena gracilis under stress was recorded after the exposure to metals such as cadmium, tributyltin chloride and uranium. E. gracilis can change its spindle form to cyst, star and V-shape when the cell is under chemical stress (Ohta M et al 2001;Watanabe and Suzuki 2001;Ohta and Suzuki 2007;Trenfield et al 2012).…”
Section: Euglena Gracilis Z and Smz As In-vivo Modelsmentioning
confidence: 99%
“…Furthermore, CuSO 4 was more toxic to the Z strain than SMZ strain in K-H medium. In both media Z and SMZ cells showed limited toxicity to ZnSO 4 (as a control for zinc-cyanide complex mixed species toxicity) which may be explained by the high concentration of organic matter and glucose in K-H medium which can interfere with metal toxicity (Trenfield et al 2012), or due to the use by specific enzymes of zinc which is an essential micronutrient for eukaryotic cell (Leeson 2009). …”
Section: Comparison Composite and K-h Mediamentioning
confidence: 99%